Polish-Ukrainian Cooperation in the Scope of Spatial Planning - Dagmara Kociuba (Barometr Regionalny)
The following paper summarises Polish experience related to current cross-border cooperation in the scope of spatial planning. The first part presents the legal basis of cross-border cooperation and strategic-planning documents developed so far. The second part focuses on cooperation with the Ukrainian side, both at the level of state administration and working groups developing elaborations for both parts of the border region. It includes a detailed description of the development of one of them — the map of investment projects of the Polish part of the Polish-Ukrainian border region. It presents the scope of works, manner of preparing the maps and the text, and results of the works.